Legal Protection of Personal Data Against Phishing in Indonesia: A Pancasila-Based Approach - Gunsu Nurmansyah; Rudi Natamiharja; Ikhsan Setiawan (Pancasila and Law Review, 2025)
Phishing in Indonesia presents significant risks to privacy and data security. This study employs a normative juridical approach to analyze the protection of personal data, with attention to both preventive and repressive legal mechanisms. It assesses the effectiveness of Law No. 27 of 2022 on Personal Data Protection in combating phishing, alongside measures of digital literacy and law enforcement. The findings indicate notable progress but highlight persistent challenges in enforcement capacity, public awareness, and international cooperation. The study recommends strengthening enforcement, expanding cybersecurity education, and enhancing cross-border collaboration to advance data protection.